Pengaruh pengeluaran Pemerintah Bidang Kesehatan Dan Pendidikan Terhadap Jumlah Penduduk Miskin Di Kabupaten/Kota Di Provinsi Kalimantan Barat Tahun 2009-2012 - B01110011, Turtinawati (Jurnal Pembangunan dan Pemerataan, 2014)
Poverty is a problem and become one of the obstacles in the construction, which is complex. So in need of appropriate and sustainable strategies in tackling the problem of poverty. The problems discussed in this study whether government spending on health and education has an influence on the number of poor people in order to determine the direction of government policies in reducing the number of poor people. This study aims to determine how much influence the government spending variables public expenditure in health and education to the number of poor people in the district / city in the province of West Kalimantan 2009-2012. The analysis used data panel regression analysis is used to examine the relationship between the variables of government spending government spending in health and education with the number of poor people in the district / city in the province of West Kalimantan. The data used are secondary data years 2009-2012 consisted of 14 district / city in the province of West Kalimantan from the Central Statistics Agency (BPS) and the Ministry of Finance. The results showed that the health sector public expenditure not significant effect on the number of poor people obtained t value of (-0.042769> 0.05). Government spending in education have a significant effect on the number of poor people t value of (-2.161004 <0.05). The test results simultaneously obtained Fstatistik value of 2.468864 to the value of prob (Fstatistik) of 0.094369 is greater than 0.05 (probability> 0.05). This means that the number of poor people is not affected by government spending on health and education together. Keywords: Government Spending of Social Affairs, the Poor.